ACUTE URTICARIA IN CHILDREN - Barros de Sá, Janilson; Guilherme de Sá Santos, João; Carvalho de Sá, Vinicius (Health and Society, 2024)
Acute urticaria is a common condition in children, characterized by itchy skin lesions that appear suddenly. Although usually self-limiting, it can cause significant discomfort. Triggers include infections, food allergies, and drug reactions. Management mainly involves antihistamines, with corticosteroids in more severe cases. A systematic analysis of the literature is necessary to optimize the diagnosis and treatment of acute urticaria, seeking to consolidate evidence that helps health professionals in clinical practice. This research uses the systematic literature review method, with the objective of gathering and analyzing the most relevant studies on acute urticaria in children published between 2014 and 2024. Acute urticaria presents with urtices rashes, pruritic, and angioedema alone or in association with urtices. It can be triggered by infections, food allergies, or medications, but often the cause is idiopathic. Most episodes are self-limiting, with symptoms that disappear in less than 24 hours. Educating caregivers about possible triggers and monitoring allergic reactions are key to effective treatment. Acute urticaria in children is common but often underdiagnosed. Although most cases are self-limiting, identifying triggering factors is crucial to preventing recurrences. Proper management is critical for treatment. Educating caregivers about the condition and seeking medical attention in serious situations are essential to ensure the child’s well-being.